Probabilistic analysis of a standby system subject to inspection and maintenance under Weibull laws - Bhardwaj, R. K.; Kaur, Mandeep; Singh, Ravinder (AIP conference proceedings, 2023)
An effective provision of inspection and maintenance is always rewarding in the form of highly reliable systems and a good switching add on more benefits by making it more cost effective. The present paper analyzes various system performance indices a server is part of a standby system made up of two similar components and a reparable switch. Both of the units undergo inspection after failure to check their feasibility for repair, replacement or maintenance. The model is developed using a semi-Markov process and the regenerating point approach. Particular cases are derived using Weibull distribution and results are illustrated in the form of tables. The concluding remarks regarding impact of Weibull parameters have also been included.